Comprehensive management strategy of interstitial lung disease induced by trastuzumab deruxtecan - ZHANG Jian, HAN Qian, XU Fei, GAN Lu, CHEN Zhanhong, MA Li, WANG Hao, LIU Jieqiong, WU Xiaohong, CAI Li, ZHAO Bing, LÜ Zheng, LI Li, NI Sujie, HU Xichun (Zhongguo aizheng zazhi)
Trastuzumab deruxtecan (T-DXd) has demonstrated significant efficacy in clinical trials for human epidermal growth factor receptor 2 (HER2)-expressing breast cancer, gastric cancer, lung cancer and other solid tumors. Its overall safety profile is manageable and tolerable, including the clinically concerning interstitial lung disease (ILD). The etiology of ILD is varied, among which drug-induced ILD is an exclusionary diagnosis. The incidence of ILD caused by different antitumor drugs varies with different symptoms, and the pathogenesis remains unclear. T-DXd-induced ILD is mostly Grades 1-2, and implementing a standardized clinical management protocol can reduce the incidence of severe ILD events, improve patient prognosis, and help maximize the clinical benefits of T-DXd. This article summarized the epidemiology, etiology, risk factors, and potential mechanisms of drug-induced ILD, with a focus on the incidence, time to onset, and outcomes of T-DXd-induced ILD after standardized clinical management. It aimed to help readers understand the importance of standardized clinical management before and during T-DXd treatment. Regarding specific clinical management strategies, the article reviewed comprehensive management approaches for T-DXd-induced ILD based on clinical trial protocols and real-world experiences from both domestic and international perspectives, covering patient screening, patient education, ILD monitoring, diagnosis, and treatment. Before initiating T-DXd treatment, patient screening helps identify those at high risk for ILD, and T-DXd should be used cautiously in these high-risk patients. Effective patient education can enhance patient initiative, encouraging them to promptly report suspected symptoms, which contributes to early identification of ILD. During T-DXd treatment, it is important to regularly monitor symptoms and signs related to ILD, implement regular imaging monitoring and leverage multidisciplinary team collaboration to diagnose ILD as early as possible, thereby minimizing the risk of severe ILD. If symptoms or imaging suggest ILD, T-DXd treatment must be immediately interrupted, and relevant examinations should be completed to rule out other possible causes while considering corticosteroid treatment. Upon ILD diagnosis, subsequent T-DXd dose adjustments, corticosteroid therapy, and supportive treatments should be guided by severity. The article also explored whether patients with T-DXd-induced ILD can be re-treated, concluding that Grade 1 ILD patients might be eligible for re-treatment under specific conditions. In conclusion, the article reviewed the epidemiology, characteristics, clinical trial-recommended management strategies, and real-world management measures of T-DXd-induced ILD, integrating clinical expert experiences to summarize and discuss comprehensive management strategies for it. This aimed to enhance clinicians' understanding of T-DXd-induced ILD and provide valuable insights for early identification, timely diagnosis, and proper management of it.